Insomnia in Adults During COVID-19 Pandemic and Its Association with Social Media Addiction - Songül Duran; Serap Kaynak (Türk Uyku Tıbbı Dergisi, 2022)

(untitled)
Objective:There are concerns that the use of social media may have increased as a result of the prolonged stay-at-home period to ensure social isolation during Coronavirus disease-2019 (COVID-19), leading to social media addiction, which may cause insomnia. However, studies in this field are limited. Therefore, the main purpose of this study is to eliminate this gap in the literature by examining the cross-sectional and longitudinal relationships between social media addiction and insomnia in adults.Materials and Methods:Data was collected using an online survey administered in February 2021. The questionnaire measured demographic variables, insomnia, social media addiction. The sample in the present study consisted of 405 participants.Results:Insomnia scores were found to be higher in women, singles, unemployed, unborn children, and those who had a relative with COVID-19. Social media addiction is higher in singles, unemployed and those without children. Having a close relative with coronavirus has been associated with social media addiction.Conclusion:Considering the negative impact on insomnia, we recommend taking initiatives to reduce social media addiction.